Reproductive biology of Celebes rainbowfish (Marosatherina ladigesi Ahl, 1936) in some rivers of South Sulawesi - Jayadi St Hadijah; Beddu Tang; Amrah Husma (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2016)
The purpose of this study was to analyze the reproductive biology of Celebes rainbowfish (Marosatrherina ladigesi) in some rivers of South Sulawesi including sex ratio, fecundity, eggs diameter, gonado somatic index, gonad maturity sta- ges, and spawning season. Fish collections were conducted in the Bantimurung River, Sawae River, Asanae River, and Jenae River. This study was conducted for one year from January to December 2014. Fish samples were separated by sex, total length was measured using calliper with a precision of 0.1 mm, while the body weight and gonad weight were measured with analytical balance with a precision of 0.01 g. Gonads were preserved in formaldehyde 4% for the deter- mination of fecundity, eggs diameter, gonad maturity index, and gonad maturity level. Sex ratio was unbalanced in every month and fecundity of fish ranged between 98-978 eggs. Relationship between fecundity and body length was strongly correlated, while the relationship between fecundity with body weight was weakly correlated. Fish eggs diameter was vary and this fish categorized as partial spawner. Gonad maturation index of males and females increase in August, September, October, November, December and January. Mature fish was collected in every month of sampling period and the peak spawning season was found in December Abstrak Tujuan penelitian ini untuk menganalisis biologi reproduksi ikan beseng-beseng di Sulawesi Selatan meliputi nisbah ke- lamin, fekunditas, diameter telur, indeks kematangan gonad, tingkat kematangan gonad, dan musim pemijahan. Lokasi pengambilan sampel meliputi Sungai Bantimurung, Sungai Sawae, Sungai Asanae, dan Sungai Jenae. Penelitian dilaku- kan selama satu tahun mulai Januari sampai Desember 2014. Pengambilan sampel ikan menggunakan alat tangkap se- ser. Sampel ikan yang tertangkap dipisahkan berdasarkan jenis kelamin dan diukur panjang total, bobot tubuh, bobot gonad dan fekunditas. Pengukuran panjang total ikan menggunakan mistar geser berketelitian 0,1 mm, sedangkan bobot tubuh dan bobot gonad menggunakan timbangan analitik berketelitian 0,01 g. Gonad diawetkan dalam larutan formalin 4%, untuk penentuan fekunditas, diameter telur, indeks kematangan gonad, dan tingkat kematangan gonad. Nisbah ke- lamin tidak seimbang pada setiap bulan dan fekunditas ikan berkisar antara 98-978 butir. Hubungan fekunditas dengan panjang tubuh ikan berkorelasi erat, sedangkan hubungan fekunditas dengan bobot tubuh berkorelasi lemah. Sebaran diamater telur bervariasi dan tipe pemijahan tidak serentak. Indeks kematangan gonad ikan jantan dan betina meningkat pada bulan Agustus, September, Oktober, November, Desember dan Januari. Ikan yang yang matang gonad ditemukan setiap bulan pengamatan dan puncak pemijahan terjadi pada bulan Desember.